Physiological arousal and sensorimotor syncronisation : an investigation employing resonance frequency breathing - Wright, Shannon (2018)
It is common for individuals to move their bodies in time with external cues such as sound or music, a phenomenon known as sensorimotor synchronisation. However, not all time intervals are optimal for synchronisation, with some being too short and some being too long to effectively track and time one’s actions to. Moreover, cues often have varying periods meaning individuals must correct their movements to re-synchronise with the new rhythm. The ability to synchronise and re-synchronise thus requires correct time interval tracking. Changes in physiological arousal level have been linked to time perception and a number of investigations into the effect of meditation on time perception have been undertaken. Yet, little is known empirically as to how alterations to systems involved in time tracking affect sensorimotor synchronisation. The primary aim of this study is therefore to investigate how a shift in physiological arousal impacts sensorimotor synchronisation with rhythmically-stable and rhythmically-shifting sounds. To this end, participants performed a finger-tapping synchronisation task after either a breathing intervention or sitting quietly. The breathing intervention used was resonance frequency breathing, which increases heart rate variability and creates a parasympathetic-dominant, relaxed state of being. Circular statistics were used to generate mean phase angles and variability of finger taps relative to the sound onsets while a circular analogue of Hotelling’s T2 sample test was used to detect differences in synchronisation between conditions. No differences in synchronisation or re-synchronisation were found between conditions; additionally, physiological arousal and heart rate variability showed no significant correlation with synchronisation and re-synchronisation performance. The findings are discussed in the context of other research into time perception and altered states of consciousness. Recommendations for using resonance frequency breathing as a manipulation in future sensorimotor synchronisation research are given.